Mechanically robust, hydrothermal aging resistant, imine-containing epoxy thermoset for recyclable carbon fiber reinforced composites. (December 2022) - Liu, Yingying; Lu, Fei; Xu, Ningdi; Wang, Baolong; Yang, Lei; Huang, Yudong; Hu, Zhen
Graphical abstract: Highlights: A novel imine-containing hardener with definite structure was synthesized without catalyst. The developed epoxy thermosets with high cross-linked density exhibited improved thermal and mechanical properties. The thermosets possessed favorable hydrothermal/UV aging resistance, providing a reference for other degradable thermosets. The high-performance carbon fiber reinforced composite was recycled efficiently based on imine-containing epoxy network. Abstract: Imine compounds have been proved to possess great potential in the design and preparation of sustainable epoxy thermosets. However, it is still a great challenge to develop imine-containing hardener with definite structure due to the randomness of condensation reaction between aldehydes and primary amines. Herein, a novel amine hardener containing imine bond is synthesized successfully by selecting 4-imidazole formaldehyde and 3-aminobenzylamine as raw materials. The asymmetric structure of raw material can avoid uncontrollable reaction and ensure that this hardener possesses definite chemical structure. Due to high activity of hardener, the resultant epoxy thermosets with high cross-linked density exhibit excellent thermostability and fine hydrothermal aging resistance. Furthermore, such thermosets show good mechanical properties (tensile strength of ∼76 MPa), which are comparable to that of commercial Diglycidyl Ether of Bisphenol A epoxy resin cured by 4, 4-Diaminodiphenyl methane. More interestingly, increasing the equivalent ratio of active hydrogen to epoxy can introduce more dynamic covalent C=N linkage into the cross-linked network, thus the epoxy thermoset further achieves the decomposition within 3 h and the corresponding composite laminates also are recycled efficiently under mild condition. This work demonstrates the feasibility and potential of preparing high-performance degradable epoxy thermoset and corresponding recyclable composites based on well-designed imine-containing hardener.